A SYSTEMATIC REVIEW OF RESEARCH ON TEACHING ANXIETY - Aydin, Selami (International Online Journal of Education and Teaching, 2021)
It is evident that teaching anxiety is a significant affective state that may have profound effects on both the learning and teaching processes. However, there is no conclusive evidence regarding the sources and effects of teaching anxiety in an educational context. This systematic review aims to present an overview of the current literature on teaching anxiety, explore the variables that may relate to teaching anxiety in terms of its causes and effects. The study concludes that teaching anxiety is directly related to affective states, while the relationship between teaching anxiety levels and demographic variables is not clear. Another conclusion is that teaching experience, content knowledge, and instruction are effective for decreasing the levels of teaching anxiety. The results also show that teachers’ and students’ characteristics, teaching strategies, time and classroom management, planning, school climate, and the use of technology have considerable effects on teaching anxiety.